COMMUNITY-BASED DIGITAL MARKETING EMPOWERMENT: A HOLISTIC STRATEGY FOR EMPOWERING RURAL WOMEN MSMES IN SOUTHEAST ASIA - Endang Styawati; Eka Rahayuningsih (Asosiasi Dosen Muda Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have significantly contributed to the development of digitalization, which has spurred economic growth globally, including in Southeast Asia. However, Why rural women-led MSMEs face considerable challenges, such as limited digital literacy, the double burden of work and domestic responsibilities, and restricted access to the digital ecosystem. This study aims to develop a comprehensive community-based strategy to support village women's MSMEs through digital marketing. The article presents a conceptual model for